Freedom of information law enforcement in Nigeria: emerging issues from court cases (2017)
The promotion of access to information has become an entrenched feature of most democratic societies. This is against the backdrop of the appreciation of the value of information as a veritable tool for fostering transparency and accountability in governance. Freedom of information legislation has been enacted across the world to guarantee and promote the right of access to information and it has become the hallmark of a democratic society. In Nigeria, the Freedom of Information (FOI) Act was enacted in May 2011 after a long and tortuous sojourn in the Nigeria’s federal legislative houses of a bill erroneously perceived as the Media Bill probably because the struggle for its passage was championed by Media Rights Agenda and. some other civil rights societies in the country. The euphoria that greeted the enactment of the law having subsided, attention shifted naturally to the implementation and enforcement of the provisions of the law. Since its enactment, cases have arisen in Nigerian courts bordering on the exercise of the right of access guaranteed by the law in situations where applications for record or information have been refused. This study navigated through court decisions in some of the cases instituted to challenge denial of access to information under the FOI Act with a view to underpinning the issues raised and canvassed on the relevant provisions of the law. An analysis of the decisions was undertaken and the pronouncement of presiding judges on the issues canvassed highlighted. Based on the issues arising and the position of the court on them, recommendations were made that could impact positively on the implementation of the FOI Act in Nigeria.